Are homosexuals discriminated against in the hiring process - Ali Ahmed; Lina Andersson; Mats Hammarstedt (Institute for Labour Market Policy Evaluation (IFAU), 2011)
This paper presents the first field experiment on sexual orientation discrimination in the hiring process in the Swedish labor market. Job applications were sent to about 4,000 employers in 10 different occupations in Sweden. Gender and sexual orientation were randomly assigned to applications. The results show that sexual orientation discrimination exists in the Swedish labor market. The discrimination against gays and lesbian varies across different occupations and appears only in the private sector. The results also seem to suggest a new dimension of traditional gender roles; the gay applicant was discriminated against in typical male-dominated occupations whereas the lesbian applicant was discriminated against in typical female-dominated occupations. Thus, the results suggest that gays to some extent face the same obstacles on the labor market as heterosexual women.
Keywords: C93; J15; J71; 330; Labor market discrimination; sexual orientation; field experiment; Homosexualität; Personalbeschaffung; Arbeitsmarktdiskriminierung; Feldforschung; Schweden